1996 Proceedings 46th Electronic Components and Technology Conference
DOI: 10.1109/ectc.1996.517377
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic criterion for level-1 crack-free package-proposal of a superior package structure

Abstract: A synthetic criterion to provide guidance for the high-reliability structure design for the level-1 crackfree package is introduced. The criterion reflects a consideration of both delamination and package cracking. According to the criterion, to prevent delamination is the most effective means to realize the level-1 crack-free package for large chips (ex.15" square). Therefore, a new package structure, a chip side support (CSS) structure which eliminates a die-pad is proposed and reliability tests are carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Vent hole packages recently tested passed the 85 C/85%RH condition using the 230 C solder dip test. Inoue et al [14] showed that improved surface cleaning processes will improve the popcorn performance.…”
Section: Critical Moisture Concentrationmentioning
confidence: 99%
“…Vent hole packages recently tested passed the 85 C/85%RH condition using the 230 C solder dip test. Inoue et al [14] showed that improved surface cleaning processes will improve the popcorn performance.…”
Section: Critical Moisture Concentrationmentioning
confidence: 99%
“…Numerous studies in the literature [27][28][29][30][31][32][33][34][35][36][37] reported the damaging effect caused when plastic packages are stored in a noncontrolled humidity environment. During solder reflow of surface mount devices, the temperature of package is raised to more than 220°C (see Figure 2.4).…”
Section: Moisture Diffusion Modelingmentioning
confidence: 99%
“…The oxidation of the leadframe causes poor adhesion to the EMC, which degrades package reliability during the reflow soldering process [31. To obtain g o o d reliability with copper leadframe, preventing package delamination and cracking is the greatest challenge [4]. The critical issue for package reliability during reflow soldering is improving adhesion at the interface of copper leadframe and EMC.…”
Section: Introductionmentioning
confidence: 99%